The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1176/appi.neuropsych.14060132
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anxiety and Affective Spectrum Disorder of Mind and Body—The ALPIM (Anxiety-Laxity-Pain-Immune-Mood) Syndrome: A Preliminary Report

Abstract: The authors describe a spectrum disorder comprising a core anxiety (A) disorder and four domains: joint laxity (L), chronic pain syndromes (P), immune disorders (I), and mood disorders (M)-dubbed the ALPIM syndrome. This study examined 76 consecutive outpatients with an anxiety disorder plus at least one somatic condition from three domains. More than 80% of the patients had panic attacks, fibromyalgia, and major depressive episodes. Associations were found between joint laxity and bipolar III, headache with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Models including both somatic and also psychiatric/psychological characteristics are required. A first approach was made through the ALPIM spectrum proposal, which is the acronym for anxiety and the domains of its most commonly occurring comorbidities: JHS/hEDS, pain disorders, immune disorders, and mood disorders [Coplan et al, ]. The authors of this study hypothesized that the ALPIM syndrome have predictable psychiatric and medical comorbidities and found that significant associations between joint hypermobility and bipolar III, headache with bipolar II, and bipolar II with chronic fatigue syndrome.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Models including both somatic and also psychiatric/psychological characteristics are required. A first approach was made through the ALPIM spectrum proposal, which is the acronym for anxiety and the domains of its most commonly occurring comorbidities: JHS/hEDS, pain disorders, immune disorders, and mood disorders [Coplan et al, ]. The authors of this study hypothesized that the ALPIM syndrome have predictable psychiatric and medical comorbidities and found that significant associations between joint hypermobility and bipolar III, headache with bipolar II, and bipolar II with chronic fatigue syndrome.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major symptoms included cognitive impairments (attention, memory, processing speed, concentration/executive functioning), tactile hypersensitivity, sun sensitivity, orthostatic hypotension, weight loss, fatigue, non-restorative sleep, pelvic pain, difficulty urinating, headaches peripheral neuropathy, muscle atrophy, cervical radiculopathy, hair loss, costochondritis, subluxation of multiple joints, and generalized pain. After more thorough assessments, the eventual diagnosis was late stage Lyme borreliosis with multisystem symptoms, porphyria, Ehlers-Danlos/ALPIM syndrome (anxiety-laxity-pain-immune-mood) [56] with seizures caused by increased intracranial pressure from cranio-cervical instability. On closer evaluation, the patient had complex partial seizures and did not have "pseudoseizures".…”
Section: Case Presentationsmentioning
confidence: 99%
“…[16] A relationship was determined between five potentially pathophysiologically linked domains: anxiety disorders, joint laxity, chronic pain disorders, immune dysfunction, and mood disorders. [7] A recent study exploring psychiatric and somatic phenotype of BPAD with co-morbid anxiety disorder found hypermobile joints in 41% of the sample, and it was significantly associated with somatosensory amplification. [8] The commonly used medications for these symptoms, such as antidepressants for anxiety symptoms and steroids for pain symptoms, can have a negative impact on the course of BPAD.…”
mentioning
confidence: 99%
“…7. Agopian AJ, Tinker SC, Lupo PJ, Canfield MA, Mitchell LE.…”
mentioning
confidence: 99%